Andar y desandar sobre la victimología del cibercrimen (dos décadas después) - Reyna Alfaro, Luis Miguel (2025)
Cybercrime is a particularly complex criminal phenomenon, and one in which the criminal justice system faces its greatest challenges and difficulties. One of these concerns the victim of crime, a central actor in the dynamics of crime, whose dimension is crucial for shaping criminal policy designs. This study provides an initial approach to the development of cybercrime victimology as a central tool of criminological knowledge that should serve as a guideline for legislative responses to cybercrime.